Effect of Different pH Media on Fluoride-releasing of Silver Diamine Fluoride in Primary Teeth: An in Vitro Study - Atheer Alboeid; Nawal Alamri; Mazin Al Gahtani; Maria Salem Ibrahim; Abdul Samad Khan; Balgis Osman Gaffar (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To investigate the effect of different pH media on the concentration of fluoride-released ions from silver diamine fluoride (SDF) after its application on the enamel surface of primary molars. Material and Methods: A total of 33 specimens were prepared in sectioned parts of primary molar teeth with the following measurements (4×4 mm in height and width). Each specimen was immersed in an airtight polyethylene bottle containing 2 mL of pH media (neutral, alkaline, and acidic). The fluoride release pattern of each sample was taken on days 1, 2, 7, 15, and 30 using an Orion fluoride ion-selective electrode. Results: On day 1, acidic media showed the least mean fluoride release (8.83 ppm) compared to neutral (23.17 ppm) and alkaline media (18.92 ppm). There was a persistent decrease in the mean fluoride release at all time intervals for each media. On day 30, the fluoride release of acidic, neutral, and alkaline media was 0.477 ppm, 3.325 ppm, and 4.183 ppm, respectively. The acidic media showed a significant decrease in fluoride release (p=0.001) from day 1 to day 30 compared to neutral and alkaline media. However, non-significant differences were observed between neutral vs. alkaline media at all time intervals. Conclusion: The neutral group showed the highest fluoride release compared to other groups, where the different pH media strongly affect fluoride release from SDF material.